PENGARUH PENERAPAN METODE KONSTRUKSI MODULAR TERHADAP EFISIENSI WAKTU DAN BIAYA DALAM PROYEK KONSTRUKSI BANGUNAN - Edison Hatoguan Manurung; Angga Febriadi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The modular construction method is an innovation in the construction industry aimed at increasing project efficiency. This study aims to analyze the effect of implementing the modular construction method on time and cost efficiency compared to conventional construction methods. The study used a quantitative descriptive approach, using a case study of the construction of an office building in Grabag District, Purworejo Regency. Data were obtained from cost planning documents (RAB), project scheduling, and relevant supporting literature. The cost analysis showed that the modular method required a cost of Rp3,646,018,620.52, an 18.11% increase compared to the conventional method of Rp3,086,929,413.11. However, in terms of time, the modular method was able to shorten the construction duration from 150 days to 87 days, a 42% increase. The results showed that the modular method was superior in terms of time efficiency, while the conventional method was more economical in terms of cost. The choice of construction method should be adjusted to project priorities.